Enhancing therapeutic reasoning: key insights and recommendations for education in prescribing - Hartjes, Mariëlle G; Richir, Milan C; Cazaubon, Yoann; Donker, Erik M; van Leeuwen, Ellen; Likic, Robert; Pers, Yves-Marie; Piët, Joost D; De Ponti, Fabrizio; Raasch, Walter; van Rosse, Floor; Rychlícková, Jitka; et al. (BMC medical education, 2024)
BACKGROUND: Despite efforts to improve undergraduate clinical pharmacology & therapeutics (CPT) education, prescribing errors are still made regularly. To improve CPT education and daily prescribing, it is crucial to understand how therapeutic reasoning works. Therefore, the aim of this study was to gain insight into the therapeutic reasoning process. METHODS: A narrative literature review has been performed for literature on cognitive psychology and diagnostic and therapeutic reasoning. RESULTS: Based on these insights, The European Model of Therapeutic Reasoning has been developed, building upon earlier models and insights from cognitive psychology. In this model, it can be assumed that when a diagnosis is made, a primary, automatic response as to what to prescribe arises based on pattern recognition via therapy scripts (type 1 thinking). At some point, this response may be evaluated by the reflective mind (using metacognition). If it is found to be incorrect or incomplete, an alternative response must be formulated through a slower, more analytical and deliberative process, known as type 2 thinking. Metacognition monitors the reasoning process and helps a person to form new therapy scripts after they have chosen an effective therapy. Experienced physicians have more and richer therapy scripts, mostly based on experience and enabling conditions, instead of textbook knowledge, and therefore their type 1 response is more often correct. CONCLUSION: Because of the important role of metacognition in therapeutic reasoning, more attention should be paid to metacognition in CPT education. Both trainees and teachers should be aware of the possibility to monitor and influence these cognitive processes. Further research is required to investigate the applicability of these insights and the adaptability of educational approaches to therapeutic reasoning.
Keywords: lékové předpisy; Drug Prescriptions; klinické kompetence; Clinical competency; Clinical pharmacology and therapeutics; Medical education; Clinical Competence; Therapeutic reasoning; medikační omyly; klinická farmakologie; Education, Medical, Undergraduate; Medical decision making; Humans; Clinical Reasoning; Management reasoning; studium lékařství pregraduální; metakognice; Metacognition; Medication Errors; klinická rozvaha; Pharmacology, Clinical; lidé